Utilization of overripe bananas for fruit sheets development (Musa spientum Va. Lacatan) - Pinga, Susan D.
Overripe bananas (lacatan variety) were pureed and dehydrated into fruit sheets. Six combinations of sucrose-citric acid level were evaluated for th most acceptable blend. Subjective evaluation of the products indicated that sample with SS/TA ratio of 30°Bx-0.50% TA was most acceptable. The optimum drying time at 60 - 75°C was determined. The samples were adjusted to the most acceptable SS/TA combination and dried in a cabinet dryer for 8, 9, and 10 hours. Objective and subjective test results showed that a highly desirable fruit sheet was obtained after 9 hours of drying. Finally, the sorption isotherm curve of the product was determined using the Wink's weight equilibrium method. The curve obtained was typically sigmoidal in shape. The fruit sheet was found to be most stable at relative humidity values of 18 to 52% at 25°C.